Protective potential effects of hydroalcoholic extract of Teucrium polium L. (Lamiaceae) against paraquat-induced lung fibrosis: An experimental study in rats - Shahrzad Molavinia; Mehdi Goudarzi; Mohammad Ebrahim Azemi; Zahra Basir; Zahra Nazari Khorasgani; Mohammad Reza Rashidi Nooshabadi; Rezvan Ebrahimi; Mohammad Javad Khodayar (Mashhad University of Medical Sciences, 2023)
Objective: Paraquat (PQ) is a highly toxic herbicide that causes pulmonary fibrosis (PF), and no specific antidote is available against it. Teucrium polium L. is a plant that exhibits antioxidant and anti-inflammatory activities. The present study evaluates the preventive and therapeutic effects of T. polium extract (TPE) against PQ-induced lung fibrosis in rats.Materials and Methods: We divided rats into five groups of eight. Groups one and two received saline and PQ (20 mg/kg, i.p.), respectively. Groups three to five were treated with TPE (50, 100, and 200 mg/kg, by gavage) started one week before PQ administration and lasted three weeks after PQ administration.Results: Our findings showed that PQ significantly increased lung malondialdehyde, nitric oxide, hydroxyproline, lung index, Ashcroft score, red blood cells accumulation, and inflammatory cell infiltration. Moreover, PQ decreased catalase and glutathione peroxidase activities and glutathione content. The results of hematoxylin-eosin and Masson's trichrome staining indicated that PQ destroyed lung parenchyma and developed PF (p<0.05 to p<0.001). Gavage with TPE significantly improved biochemical and histological abnormalities induced by PQ in rats (p<0.05 to p<0.001).Conclusion: The current survey indicated that treatment with TPE could reduce and reverse PQ-induced PF, which may be due to the phenolic compounds present in TPE.